2017
DOI: 10.1002/slct.201701818
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Carbamate Annulation for the Synthesis of 2,5‐Dideoxy‐2,5‐iminoglycitols

Abstract: A combination of the Vasella‐reductive‐amination and carbamate annulation reactions was applied on a ketose starting material for the diastereoselective total synthesis of 2,5‐dideoxy‐2,5‐imino‐glycitols. The synthesis of 2,5‐dideoxy‐2,5‐imino‐l‐iditol (4) was particularly expedient (6 steps and 18% overall yield) as the route minimises the use of protecting groups, thereby reducing the number of synthetic steps and increasing the overall yield. The Vasella reductive amination methodology could be readily appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…17 Several years later, it was shown that 6-deoxy-6-benzyloxycarbonylamido-ketose 6b 26 or 6deoxy-6-azido-ketose 6c, prepared either enzymatically 27 or chemically, 28 provided convenient access to DNJ (2) using the same hydrogenation strategy, again with exclusive formation of the gluco-isomer, and others have subsequently developed routes for the synthesis of polyhydroxypiperidines utilizing iminium ions as key reactive intermediates. 29 Building on the aforementioned studies and our experience with iminosugar synthesis from ω-deoxy-ω-iodo-glycosides, 30,31 we envisioned that iodo-glycosides would be ideal starting materials for a cascade reaction leading to the efficient syntheses of a variety of iminosugars with minimal use of protecting groups (Scheme 2). Key in our approach is the avoidance of elaborate protecting-group strategies and functional group interconversions to reach the imine intermediate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Several years later, it was shown that 6-deoxy-6-benzyloxycarbonylamido-ketose 6b 26 or 6deoxy-6-azido-ketose 6c, prepared either enzymatically 27 or chemically, 28 provided convenient access to DNJ (2) using the same hydrogenation strategy, again with exclusive formation of the gluco-isomer, and others have subsequently developed routes for the synthesis of polyhydroxypiperidines utilizing iminium ions as key reactive intermediates. 29 Building on the aforementioned studies and our experience with iminosugar synthesis from ω-deoxy-ω-iodo-glycosides, 30,31 we envisioned that iodo-glycosides would be ideal starting materials for a cascade reaction leading to the efficient syntheses of a variety of iminosugars with minimal use of protecting groups (Scheme 2). Key in our approach is the avoidance of elaborate protecting-group strategies and functional group interconversions to reach the imine intermediate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Building on the aforementioned studies and our experience with iminosugar synthesis from ω-deoxy-ω-iodo-glycosides, , we envisioned that iodo-glycosides would be ideal starting materials for a cascade reaction leading to the efficient syntheses of a variety of iminosugars with minimal use of protecting groups (Scheme ). Key in our approach is the avoidance of elaborate protecting-group strategies and functional group interconversions to reach the imine intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…As better access to DIA would allow for more in depth investigations into the potential of this molecule as a treatment for Fabry disease, it was desired to establish a highly efficient route for its preparation by utilising the previously developed carbamate proposed that 82 could be prepared without the need for protecting groups (R 1 = H, R 2 = Me), as the annulation strategy is amenable to such an approach, 105 however, the synthesis of iminosugars in the absence of PGs is not without its challenges 63,64 and thus, the use of PGs was also considered in the retrosynthetic plan (R 1 = R 2 = PG). Finally, methyl iodo-glycoside 82 could be prepared from commercially available D-tagatose (25).…”
Section: Retrosynthesismentioning
confidence: 99%